Labor Decision Analysis In West Sumatra - Ridho Saputra; Melty Roza Adry (Gorontalo State University, 2021)
This study aims to analysis the determinants of labor employment decisions in West Sumatra.. The data used in this study is SAKERNAS data in 2018. The variables used in this study are workforce employment decisions, education level, gender, age, and residential area. This study uses multinomial logistic regression analysis. The results of this study indicate that: (1) Education has a significant effect on employment decisions for contract wages and wages without contracts compared to entrepreneurs in West Sumatra (2) Gender significantly influences employment decisions for contract wages and wages without contracts compared to entrepreneurs in West Sumatra (3) Age has a significant effect on contractual wage employment decisions compared to entrepneurship, while age variable has no significant effect on contractual wage employment decisions compared to entrepreneurship in West Sumatra (4) The area of residence has a significant effect on wage employment decisions with contracts compared to entrepreneurship, where as variables the area of residence does not significantly influence the decision of wage employment without a contract compared to entrepreneurship in West Sumatra.